Hypertension among adolescents in sub-Saharan Africa: a systematic review - Nsanya, Mussa K.; Abramson, Rachel; Kisigo, Godfrey A.; Hickner, Andy; Nyanza, Elias C.; Peck, Robert N.; Kapiga, Saidi H. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Hypertension (HTN) among adolescents is common in high-income countries, and leads to increased premature cardiovascular diseases (CVD). In sub-Saharan Africa (SSA), the prevalence of HTN among adolescents, associated risk factors and CVD complications are not well-described. Such data is needed for planning public health programs to prevent premature CVD in SSA. Methods We systematically searched 5 databases (MEDLINE, Embase, Google Scholar, Web of Science, and African Index Medicus) from their establishment to December 2021. Key search terms were: adolescent, arterial hypertension, and names of the 48 countries in SSA. We used Covidence® to manage the search results. The review was registered in the Open Science Framework (OSF) https://osf.io/p5sbt/. Results We identified 4,008 articles out of which we screened 3,088 abstracts, and reviewed 583 full-text articles. We finally included 92 articles that were published between 1968 to December 2021. The majority were cross-sectional studies (80%) and conducted in school settings (78%). The risk of bias was low for 59 studies (64.1%), moderate for 29 studies (31.5%), and high for 4 studies (4.3%). Overall, the prevalence of HTN varied widely from 0.18% to 34.0% with a median (IQR) of 5.5% (3.1%, 11.1%). It was relatively higher in studies using automated blood pressure (BP) devices, and in studies defining HTN using thresholds based on percentile BP distribution for one's height, age, and sex. In addition, the prevalence of HTN was significantly higher in studies from Southern Africa region of SSA and positively correlated with the year of publication. Across studies, traditional risk factors such as age, sex, body mass index, and physical inactivity, were commonly found to be associated with HTN. In contrast, non-traditional risk factors related to poverty and tropical diseases were rarely assessed. Only three studies investigated the CVD complications related to HTN in the study population. Conclusion The prevalence of HTN among adolescents in SSA is high indicating that this is a major health problem. Data on non-traditional risk factors and complications are scarce. Longitudinal studies are needed to clearly define the rates, causes, and complications of HTN. Systematic Review Registration https://osf.io/p5sbt/, identifier (10.17605/OSF.IO/P5SBT).